2021
DOI: 10.1016/j.bioactmat.2020.09.020
|View full text |Cite
|
Sign up to set email alerts
|

In vivo degradation and endothelialization of an iron bioresorbable scaffold

Abstract: Detection of in vivo biodegradation is critical for development of next-generation medical devices such as bioresorbable stents or scaffolds (BRSs). In particular, it is urgent to establish a nondestructive approach to examine in vivo degradation of a new-generation coronary stent for interventional treatment based on mammal experiments; otherwise it is not available to semi-quantitatively monitor biodegradation in any clinical trial. Herein, we put forward a semi-quantitative approach to measure degradation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…In addition, although complete bioresorption time appears to occur by 5–7 years post-implantation in a healthy porcine coronary artery, there is still room for further improvement of the nitrided iron scaffold. For example, to further shorten complete bioresorption time might be achieved via nitriding technology and be combined with biodegradable polymer to prepare metal-polymer composite scaffolds [ 12 , [28] , [29] , [30] , [31] , [32] ]. Newer iron-based bioresorbable scaffolds may hold promise among BRS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although complete bioresorption time appears to occur by 5–7 years post-implantation in a healthy porcine coronary artery, there is still room for further improvement of the nitrided iron scaffold. For example, to further shorten complete bioresorption time might be achieved via nitriding technology and be combined with biodegradable polymer to prepare metal-polymer composite scaffolds [ 12 , [28] , [29] , [30] , [31] , [32] ]. Newer iron-based bioresorbable scaffolds may hold promise among BRS.…”
Section: Discussionmentioning
confidence: 99%
“…Fe is the most abundant metal in the human body and participates in a wide variety of metabolic processes, such as oxygen transport, energy metabolism, enzyme function, and DNA synthesis [ 11 , 13 , 14 ]. In particular, it is known for its vital role in bone homeostasis, and a deficiency of Fe causes bone disorders and impairs bone mineralization [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although animal experiments have shown that there is no intravascular thrombosis or severe inflammation during the implantation of Fe-based stents (e.g. nitrided Fe-based stents) [ 21 ], they lack the support of clinical trial data. Moreover, the degradation period of Fe-based stents is too long [ 22 ], and they are extremely susceptible to the influence of magnetic fields, which makes it impossible for patients implanted with Fe-based stents to undergo MRI [ 23 ].…”
Section: Introductionmentioning
confidence: 99%